2021
DOI: 10.3389/fimmu.2021.753901
|View full text |Cite
|
Sign up to set email alerts
|

A Validation Study Comparing Risk Prediction Models of IgA Nephropathy

Abstract: We aimed to validate three IgAN risk models proposed by an international collaborative study and another CKD risk model generated by an extended CKD cohort with our multicenter Chinese IgAN cohort. Biopsy-proven IgAN patients with an eGFR ≥15 ml/min/1.73 m2 at baseline and a minimum follow-up of 6 months were enrolled. The primary outcomes were a composite outcome (50% decline in eGFR or ESRD) and ESRD. The performance of those models was assessed using discrimination, calibration, and reclassification. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The mean eGFR at baseline in our patients was lower than 60 mL/min/1.73 m 2 , which is considered an independent high-risk factor for developing end-stage renal disease 37 . Except for patient #3, the annual decline improved significantly to 4.9 mL/min/1.73 m 2 (mean), which is clinically meaningful.…”
Section: Discussionmentioning
confidence: 55%
“…The mean eGFR at baseline in our patients was lower than 60 mL/min/1.73 m 2 , which is considered an independent high-risk factor for developing end-stage renal disease 37 . Except for patient #3, the annual decline improved significantly to 4.9 mL/min/1.73 m 2 (mean), which is clinically meaningful.…”
Section: Discussionmentioning
confidence: 55%
“…Regarding Chinese, as far as we know, only one study based on a multicenter IgA nephropathy cohort and another study based on a glomerular disease-specific cohort provided data for validation. 9 , 10 Therefore, the current study represents another effort to replicate the KFRE based on a CKD cohort that stemmed from primary care settings in China, and the patients had lower uACR and higher eGFR values than the original KFRE-establishing cohorts. Consistent with the previous studies based on the non-North American equations with lower risk calibration, we also observed that the discrimination was sufficiently good (Harrell’s C statistic was above 0.75) and that the calibration was acceptable.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Previous validating studies of KFRE among Chinese patients were restricted to specific patients with IgA nephropathy or glomerular diseases. 9 , 10 Based on the electronic health record data of the China Kidney Disease Network (CK-NET)-Yinzhou study of community-dwelling residents in an eastern coastal area of China, the present study aimed to validate the accuracy of the KFRE and provide evidence for their potential clinical usage. 8 , 11 …”
mentioning
confidence: 99%
“…In the same study, the validation cohort included more patients with other races/ethnicities, with only 15.5% of the cohort being Caucasian compared with 42% in the derivation cohort, indicating that the models performed well in different ethnic, geographic, and clinical settings [ 18 ]. Several external validation studies have also reported that the International IgA Nephropathy Prediction Tool performed well in different cohorts [ 28 30 ]. Considering this evidence, the recently published Kidney Disease: Improving Global Outcomes (KDIGO) guidelines for glomerular diseases advocate the use of the International IgA Nephropathy Prediction Tool for risk quantification and shared decision-making with patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%